Supportive periodontal therapy using mechanical instrumentation or 2% minocycline gel: a 12 month randomized, controlled, single masked pilot study - E. McColl (Blackwell Synergy, 2006)
Objective: To compare the short-term performance of subgingival local delivery of 2% minocycline gel and conventional subgingival debridement in supportive periodontal therapy (SPT) patients. Methods: Forty adult patients having completed active treatment for moderate to advanced chronic periodontitis were included in a randomized, controlled, single masked maintenance care pilot study. Sites with residual pocket probing depths X5mm and bleeding on probing were treated with either minocycline gel (minocycline-group) or scaling and root planing only (debridement-group) at baseline, 3, 6, and 9 months. Clinical and microbiological examinations were performed at baseline, 3, 6, 9, and 12 months. Results: Full-mouth plaque and bleeding scores remained o10% and o20%, respectively, for both groups throughout the study. In both groups there was a persistent reduction in number of teeth and sites with probing pocket depths X5mm (po0.05) with no significant differences between the groups. The prevalence of Porphyromonas gingivalis, Tannerella forsythia, Treponema denticola, Actinobacillus actinomycetemcomitans, Prevotella intermedia, and Prevotella nigrescens, remained at levels 4105 in the majority of patients and sites in both groups. Conclusion: This pilot study failed to show a difference between local delivery of 2% minocycline gel as mono-therapy and traditional subgingival debridement in patients on SPT.